The Levels of Affective Filter In Online Language Learning Among TESL Students in Universities in Selangor - Saifu Zaman, Sharmine Arisha; Lutfi, Naqib; Ganesan, Hishalini (Selangor Humaniora Review, 2022)
In the days following the pandemic, the shift to virtual learning has posed a significant challenge for educators and pupils. However, this drastic and unexpected change has caused students to worry about their educational performance and learning efficiency. It is important to address those scholars who struggled with motivation, anxiety, and self-confidence, all of which led their affective filter levels to shift rapidly in online learning thus underachieving in the classroom due to this affective filter. Therefore, this study investigates the levels of affective filter in online language learning among TESL students in Malaysian universities. The participants were TESL students from Malaysian universities. The inputs of the study were collected through a google form questionnaire in this quantitative research. The findings indicated that access to learning devices, excitement for upcoming lessons, and challenges in learning English has affected their affective filter levels the most. To conclude, students must have learning facilities, lessons must be made easy and English lessons must be less challenging.